Computational fluid dynamics in ventilation design - Nielsen, Peter V.; Allard, Francis (REHVA guidebook ;, 2007)
CFD-calculations have been rapidly developed to a powerful tool for the analysis of air pollution distribution in various spaces. However, the user of CFD-calculation should be aware of the basic principles of calculations and specifically the boundary conditions. Computational Fluid Dynamics (CFD) - in Ventilation Design models is written by a working group of highly qualified international experts representing research, consulting and design.